Design of carbon–ceramic composite membranes with tunable molecular cut-offs from a carboxylic benzoxazine ligand chelated to silica–zirconia. Issue 9 (30th June 2022) - Lawal, Sulaiman Oladipo; Nagasawa, Hiroki; Tsuru, Toshinori; Kanezashi, Masakoto
Abstract : This study presents a concept that focuses on the structure design of preceramic resin precursors by the sol–gel method for fabricating carbon–ceramic molecular sieving membranes. Abstract : Carbon molecular sieve and composite carbon molecular sieving membranes are fabricated via the traditional methods of pyrolyzing polymers or by using preceramic composite polymers bearing macromolecular structures. Scant attention is paid to the design of the precursor structures in the tailoring of these membranes. In this study, a preceramic resin sol was formed using separate precursors that included vinyltrimethoxysilane (VTMS), zirconium n -butoxide (ZrTB), and a carboxylic benzoxazine ligand–3-(3-oxo-1, 4-benzoxazin-4-yl)propanoic acid (BZPA), which was analyzed via FTIR. Additional XPS analysis revealed the formation of sp 2 hybridized carbon structures after pyrolysis of the preceramic resin between 550 and 850 °C. A composite VTMS–ZrTB–BZPA resin sol was used to fabricate thin carbon–ceramic membranes with molecular sieving performances that could be tuned via the pyrolysis temperature, and H2 /SF6 and H2 /CH4 selectivities of 10 4 and 10 2, respectively, were achieved. This work offers a flexible method for the fabrication of high-performance carbon–ceramic composite membranes by focusing on the ground-up design of precursor preceramic polymer structures in addition to processing parameters.